Resolution, determination of enantiomeric purity and chiral recognition mechanism of new xanthone derivatives on (S, S)‐whelk‐O1 stationary phase. Issue 6 (25th April 2017) - Carraro, Maria L.; Palmeira, Andreia; Tiritan, Maria E.; Fernandes, Carla; Pinto, Madalena M.M.
Abstract: The enantioresolution and determination of the enantiomeric purity of 32 new xanthone derivatives, synthesized in enantiomerically pure form, were investigated on ( S, S )‐Whelk‐O1 chiral stationary phase (CSP). Enantioselectivity and resolution (α and RS ) with values ranging from 1.41–6.25 and from 1.29–17.20, respectively, were achieved. The elution was in polar organic mode with acetonitrile/methanol (50:50 v/v ) as mobile phase and, generally, the ( R )‐enantiomer was the first to elute. The enantiomeric excess ( ee ) for all synthesized xanthone derivatives was higher than 99%. All the enantiomeric pairs were enantioseparated, even those without an aromatic moiety linked to the stereogenic center. Computational studies for molecular docking were carried out to perform a qualitative analysis of the enantioresolution and to explore the chiral recognition mechanisms. The in silico results were consistent with the chromatographic parameters and elution orders. The interactions between the CSP and the xanthone derivatives involved in the chromatographic enantioseparation were elucidated. Abstract :